Beyond the skin: Lived experiences and coping strategies of psoriasis patients in Malaysia - Che Jusoh Che Awanis; Mohd Noor Norhayati; Zainab Mat Yudin (PLoS ONE, 2026)
Background Psoriasis is a chronic autoimmune skin condition that significantly impacts an individual’s quality of life, resulting in physical discomfort, psychological distress, and compromised social well-being. However, there is limited understanding regarding the challenges faced by patients in Malaysia. This study examines the lived experiences of patients with psoriasis in Malaysia, focusing on the emotional, social, financial, and treatment-related challenges they face, as well as the coping mechanisms they employ. Methods A qualitative, phenomenological approach was employed among members of the Psoriasis Association Malaysia. Purposive sampling was used to recruit adult participants who were capable of participating in the online interview. Data collection involved the use of Google Forms, which included the Malay version of the Dermatology Life Quality Index questionnaire, supplementing the qualitative findings. This was followed by semi-structured online interviews conducted via video conferencing. Thematic analysis was conducted using NVivo version 14, and descriptive analysis was performed using SPSS version 28. Result This study involved 30 respondents with a mean age of 44 years diagnosed with psoriasis. The mean (SD) for the duration of illness is 21.3 (11.8) years. About 70% respondents reported that psoriasis had a moderate to very high impact on their quality of life. Thematic analysis has identified six major themes, including physical devastation, emotional burden, disruption in social functioning, treatment hurdles and advancements, financial barriers, and behavioral adaptation. Conclusion Psoriasis imposes complex challenges that extend beyond physical symptoms, affecting emotional well-being, social interactions, financial stability, and treatment struggles. In response to the various challenges that arose, respondents developed behavioral adaptations to achieve a better quality of life. Framed within the biopsychosocial model, the findings emphasize the need for a holistic, patient-centred approach to psoriasis care that integrates medical treatment with psychological support and social interventions to improve overall quality of life.